2022
DOI: 10.1111/jam.15581
|View full text |Cite
|
Sign up to set email alerts
|

Container material dictates stability of bacteriophage suspensions: Light scattering and infectivity measurements reveal mechanisms of infectious titre decay

Abstract: Aims: To measure the infectious titre (IT) decay rate for various bacteriophages as a function of storage container material. Additionally, parallel light scattering and infectious titre measurements reveal distinct mechanisms for IT loss, depending on phage. Methods and Results: Suspensions of bacteriophages 44AHJD, P68 and gh-1 were stored in various labware. IT of each suspension was repeatedly measured over the course of 2 weeks. Large variability in IT decay was observed, with >4 log 10 loss in glass and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Reports concerning other biomolecules assume the conformation in which biomolecular hydrophobic parts are in contact with the hydrophobic surface, whereas the more hydrophilic regions of the molecule are exposed to bulk (and water) (Rabe et al, 2011). O'Connell et al (2022) showed the effect of containers on phage titer, but they suggested that the topology of the surface governed the adsorption of phage virions on plastic surfaces. Based on these reports, we hypothesized that virions can be scavenged also by microplastic particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports concerning other biomolecules assume the conformation in which biomolecular hydrophobic parts are in contact with the hydrophobic surface, whereas the more hydrophilic regions of the molecule are exposed to bulk (and water) (Rabe et al, 2011). O'Connell et al (2022) showed the effect of containers on phage titer, but they suggested that the topology of the surface governed the adsorption of phage virions on plastic surfaces. Based on these reports, we hypothesized that virions can be scavenged also by microplastic particles.…”
Section: Resultsmentioning
confidence: 99%
“…O'Connell et al. (2022) showed the effect of containers on phage titer, but they suggested that the topology of the surface governed the adsorption of phage virions on plastic surfaces. Based on these reports, we hypothesized that virions can be scavenged also by microplastic particles.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, a phage-functionalized gold layer can easily approach the geometric limits of surface density when cross-linked to the surface with 11-MUA if special consideration is paid to upstream purification of the phage suspensions. Additionally, it is important to consider the impact of container material used for storage of phage suspensions as it has recently been shown that infectious titer can drop dramatically in the interval between the measurement of titer and immobilization depending on the container material …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is important to consider the impact of container material used for storage of phage suspensions as it has recently been shown that infectious titer can drop dramatically in the interval between the measurement of titer and immobilization depending on the container material. 87 The immobilization of phages on appropriate substrates can be leveraged to detect a large variety of analytes, to reduce bioburden surrounding wounds, 88 and to prevent spoiling of food 2,3,89 and wine. 90 Phages can be engineered to express eukaryotic viral proteins on their surface to produce potent vaccines 91 or even attack these viruses directly.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…is controlled for since all phages are immobilized on the same surface. Phage titer can be unstable in aqueous suspensions, which brings the risk that otherwise identical substrates prepared on different days may be incubated with phage suspensions with different aggregation states and/or infectious titers [37,38]. Any differences in the phage response between the two chambers can reliably be considered to originate in the divergent response of each phage to each challenge strain, providing strong preliminary support for the feasibility of the proposed method of susceptibility testing.…”
Section: Sprmentioning
confidence: 96%